Development and validation of dissolution testings in acidic media for rabeprazole sodium delayed-release capsules. (2nd October 2016) - Tan, Yinhe; Si, Xiaoqing; Zhong, Lulu; Feng, Xin; Yang, Xinmin; Huang, Min; Wu, Chuanbin
Abstract: Rabeprazole sodium (RAB) dissolved in acidic media is accompanied by its degradation in the course of dissolution testing. To develop and establish the accumulative release profiles of ACIPHEX ® Sprinkle (RAB) delayed-release capsules (ACIPHEX ® Sprinkle) in acidic media using USP apparatus 2 (paddle apparatus) as a dissolution tester, the issues of determination of accumulative release amount of RAB in these acidic media and interference of hydroxypropylmethyl cellulose phthalate were solved by adding appropriate hydrochloric acid (HCl) into dissolution samples coupled with centrifugation so as to remove the interference and form a solution of degradation products of RAB, which is of a considerably stable ultraviolet (UV) absorbance at the wavelength of 298 nm within 2.0 h. Therefore, the accumulative release amount of RAB in dissolution samples at each sample time points could be determined by UV-spectrophotometry, and the accumulative release profiles of ACIPHEX ® Sprinkle in the media of pH 1.0, pH 6.0, and pH 6.8 could be established. The method was validated per as the ICH Q2 (R1) guidelines and demonstrated to be adequate for quality control of ACIPHEX ® Sprinkle and the accumulative release profiles can be used as a tool to guide the formulation development and quality control of a generic drug for ACIPHEX ® Sprinkle.